Pengaruh Omnichannel Experience dan Kualitas Produk terhadap Keputusan Pembelian Produk Cimory Yogurt - Dhea Pratiwi; Mukhroji Mukhroji (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Advances in digital technology have transformed the way consumers make purchase. This situation has prompted companies to focus on integrated shopping experiences across various channels (omnichannel experience) and on product quality as factors that can influence purchasing decisions. The purpose of this study is to evaluate how the omnichannel experience and product quality influence purchasing decisions regarding Cimory Yogurt. A quantitative methodology was employed, using purposive sampling technique to select a sample of 100 respondents who had previously purchased and consumed Cimory Yogurt. Research data were collected via a questionnaire and analyzed using multiple linear regression in SPSS software. The findings indicate that the omnichannel experience and product quality simultaneously have a significant influence on purchasing decisions. However, in the partial analysis, only product quality was found to have a significant effect, while the omnichannel experience did not show a statistically significant effect. These findings indicate that product quality is the most influential factor in encouraging consumers to choose Cimory Yogurt.